Towards 5G millimeter-wave wireless networks: a comparative study on electro-optical upconversion techniques - Nael A. Al-Shareefi; Jaafar A. Aldhaibaini; Sura Adil Abbas; Hadeel S. Obaid (Institute of Advanced Engineering and Science, 2020)
Fifth-generation (5G) wireless networks that use the MM−W hold a great promise to revolutionize wireless industry. However, the difficulty in generating and transmitting these high‐frequency signals in the electrical-domain due to bandwidth limitation of electronic components, and high absorption loss limits current applications. Consequently, ptical generation and transmission of MM-W signals are a viable option. In this paper, a comparative study is carried out on three electro-optical upconversion (EOU) techniques to generate 60-GHz MM-W signal, namely 4-tupling, 6-tupling and 8-tupling. The paper briefly describes the three techniques and analyses the optical harmonic distortion suppression ratio (OHDSR) and electrical spurious suppression ratio (ESSR) generated by each one of the techniques. OHDSR and ESSR have been compared to show the trade-off between the techniques. In addition, the paper compares the implementation of non−ideal phase shifting on OHDSR for the three EOU techniques. Finally, the performance of the three EOU techniques after transmission over optical fiber is evaluated by quality factor (Q-factor) and eye pattern test. The results of the simulation illustrate well the benefits of the performed study and confirm that the 4-tupling constitutes a cost-effective technique to generate MM-W signals.